Anorthosite-Farsundite Complexes in the Southern Part of the Grenville Province - Martignole, Jacques; Schrijver, Krees (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1977)
Abstract Three major anorthosite-farsundile complexes in the Grenville province underlie about 50 per cent of a northeasterly area, about 200 km long and 60 km wide, situated north of Montreal and lying parallel to the St-Lawrence River. The plutonic complexes are surrounded by a highly varied, layered assemblageofgranulite-facies country rocks, some of which, at least, are of sedimentary origin ("Grenville Supergroup"). The plutonitos were emplaced diapincally and came to rest near the interface of the pre-Grenville basement and Grenville metasediments. Diapinc rising, or lateral spreading of parts of the complexes induced large scale deformation in the country rock. Granulite faciès metamorphism took place before and during diapirtsm and lasted until about 1100 Ma ago Retrograde metamorphism due to cooling at high pressure followed diapirism. The emplacement of the crystallising plutonites is thought to be the fundamental cause of the evolution of this area in terms of deformation and metamorphism.